Relations of the Russian administration and the highest estates of the Northern Caucasus in the context of the statement of Tsar power in the region in the second half of the XIX century - Т. Ch. Dzhabaeva (Вестник Майкопского государственного технологического университета)
Analysis of the internal policy of a state in the North Caucasus, identification of positive and negative factors in the integration of the region, as well as the identification and consequences of the common interests of the tsarist administration and local feudal lords, is relevant since these processes influenced the social and economic development of the region, led to social conflicts, and in general, they changed the social and legal status of the population of the region, which was part of the legal field of the Russian Empire in the second half of the 19th century. Determining social preferences in the implementation of the agrarian policy of the tsarist administration will to some extent help to avoid this kind of social conflict in the future. The purpose of the article is to identify the social status, historical transformation, the process of strengthening and the role of the upper classes of the North Caucasus, their relationship with the new government during the second half of the 19th century, selforganization and legal status.In the process of the research work methods of comparative historical analysis, synthesis and generalization have been used, as well as the principle of objectivity and historicism, which provide the opportunity to analyze various episodes and phenomena from a historical point of view.The practice of Russian reforms in the second half of the 19th century contained a number of aspects that determined a turning point in the socio-political, socio-economic and other spheres of life of the peoples of the North Caucasus. The results of the research are the following: the claims of the upper classes to dominate the population by seizing, with the help of the new government, land holdings into their own property, as well as receiving material benefits while in service have been defined. Conclusions: the upper classes were the conductors of the policies of the Russian administration in the region, which led to social protests and the deterioration of the social situation of the dependent classes.